2017
DOI: 10.5812/ijp.5883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Classic Wiskott Aldrich Syndrome with Mild Symptoms in Two Cousins: A Case Report

Abstract: Introduction: Wiskott-Aldrich syndrome (WAS) is characterized by microthrombocytopenia, eczema, recurrent infections, and an increased incidence of autoimmunity. Commonly, classic WAS is presented with severe clinical symptoms. Case Presentation: We report a new phenotype of classic Wiskott-Aldrich syndrome with mild symptoms in two cousins who were 7 years old. They had not severe infections or hemorrhage, in spite of having genetic mutation in WAS gene. The symptoms and infections of the patients responded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Of note, T cell lymphopenia is a distinct characteristic in the ADs associated with T-cell PID disorders such as WAS [ 130 , 131 ]; however, despite its association with a variety of ADs as shown in Table 1 , T cell lymphopenia may not be present in patients who are suffering from ADs [ 132 , 133 ] due to enduring LIP and/or the concomitant occurrence of other lymphoproliferative conditions such as lymphomas [ 134 , 135 ]. It has been shown that this concomitant occurrence of lymphoproliferative conditions might be linked to treatment with methotrexate (MTX), a disease-modifying antirheumatic drug (DMARD) [ 136 , 137 , 138 ].…”
Section: Lymphopenia In Physiological and Autoimmune Conditionsmentioning
confidence: 99%
“…Of note, T cell lymphopenia is a distinct characteristic in the ADs associated with T-cell PID disorders such as WAS [ 130 , 131 ]; however, despite its association with a variety of ADs as shown in Table 1 , T cell lymphopenia may not be present in patients who are suffering from ADs [ 132 , 133 ] due to enduring LIP and/or the concomitant occurrence of other lymphoproliferative conditions such as lymphomas [ 134 , 135 ]. It has been shown that this concomitant occurrence of lymphoproliferative conditions might be linked to treatment with methotrexate (MTX), a disease-modifying antirheumatic drug (DMARD) [ 136 , 137 , 138 ].…”
Section: Lymphopenia In Physiological and Autoimmune Conditionsmentioning
confidence: 99%